Advanced Aspects - Halpin, Terry; Rugaber, Spencer (Taylor & Francis Group, 2015)
If you have completed the first three chapters of this book, you should feel comfortable programming in LogiQL. In this chapter, you will learn about some other aspects of the language useful for specialized purposes. The first unit illustrates the power and scope of the language by describing how to use LogiQL to implement some features of imperative programming languages. Some additional constraints are presented in the second unit. The third unit introduces an advanced technique, called derived entities, useful in situations where your knowledge of a particular entity comes from its properties. Although most of the examples you have seen in this book are relatively small, LogiQL can be used to develop industrial-scale applications. With this in mind, Unit 4 describes some techniques you can use for structuring large programs. The last unit presents three topics (derived-only views, hierarchical syntax, and file predicates) that do not warrant a unit of their own, but that can nevertheless be quite useful in certain circumstances. Finally, the chapter ends with a consolidation exercise giving you an opportunity to practice the skills you have learned in the chapter.